2014
DOI: 10.1124/jpet.114.218644
|View full text |Cite
|
Sign up to set email alerts
|

The Antiparasitic Drug, Potassium Antimony Tartrate, Inhibits Tumor Angiogenesis and Tumor Growth in Nonsmall-Cell Lung Cancer

Abstract: Repurposing existing drugs not only accelerates drug discovery but rapidly advances clinical therapeutic strategies. In this article, we identified potassium antimonyl tartrate (PAT), an antiparasitic drug, as a novel agent to block angiogenesis by screening US Food and Drug Administration-approved chemical drugs. By comparing the cytotoxicity of PAT in various nonsmallcell lung cancer (NSCLC) cells with that observed in primary cultured human umbilical vein endothelial cells (HUVECs), we found that HUVECs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Conceivably, due to the intense replication of this parasite during acute infection, it could be strongly affected by DNA damage or free radicals. Indeed, reports in the literature have indicated that anti-cancer drugs that affect cellular proliferation can be used as anti-microbial agents because both cell types share common behaviors concerning their high proliferative capabilities [27][28][29]. Indeed, a recent work evidenced the antileishmanial actions of other two isobenzofuranone derivatives and indicated that these actions were due to the induction of reactive oxygen species (ROS)-mediated apoptosis-like cell death and the inhibition of topoisomerases [30].…”
Section: Resultsmentioning
confidence: 99%
“…Conceivably, due to the intense replication of this parasite during acute infection, it could be strongly affected by DNA damage or free radicals. Indeed, reports in the literature have indicated that anti-cancer drugs that affect cellular proliferation can be used as anti-microbial agents because both cell types share common behaviors concerning their high proliferative capabilities [27][28][29]. Indeed, a recent work evidenced the antileishmanial actions of other two isobenzofuranone derivatives and indicated that these actions were due to the induction of reactive oxygen species (ROS)-mediated apoptosis-like cell death and the inhibition of topoisomerases [30].…”
Section: Resultsmentioning
confidence: 99%
“…The area under the curve (AUC) and incremental AUC (DAUC, defined as the AUC occurring above the baseline value) were calculated by the trapezoidal rule. Statistical differences between vehicle and single treatment groups or between single and combination treatment groups were determined by one-or two-way analysis of variance followed by Student's t test (Hwee et al, 2015;Wang et al, 2015), unless otherwise indicated in figure legends. Statistical analyses were performed using a SAS-based system (SAS Institute, Cary, NC) or Prism software (GraphPad Software, San Diego, CA).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PAT may induce the caspase-and reactive oxygen species (ROS)-dependent apoptosis of human myeloid leukemia HL-60 cells and lymphoid tumor cells (39,40). Of note, a recent study reported that PAT exerted anti-angiogenic effects on lung cancer (41). The present study revealed the significant ability of PAT to enhance the anticancer activity of CDDP in a synergistic manner, suggesting that this drug may potentially be used in combination with CDDP to improve the therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%